Syltholm VII:En atypisk beliggende Ahrensburglokalitet fra Syd-Lolland - Måge, Bjørnar (Gefjon, 2019)
The site Syltholm VII is a small hunting camp from the late palaeolithic Ahrensburgian culture. The site has been interpreted as the remains of a single stay by a group of hunters. Burnt bones from the site is dated to approx. 9500 BC. The site was